Phenylphosphine oxide containing polyimide matrix resins for atomic oxygen-resistant fiber-reinforced composites. (December 2013) - Liu, Biao; Ji, Mian; Liu, Jingang; Fan, Lin; Yang, Shiyong
Phenylethynyl-endcapped imide oligomers with different calculated molecular weights (calcd number average molecular weight (M n ‾ )) and phosphorous (P) contents (P loading) were synthesized by the reaction of diethyl ester of 4, 4′-oxydiphthalic acid, monoethyl ester of 4-phenylethynyl phthalic acid, and the P-containing diamines including [2, 5-bis(4-aminophenoxy)phenyl] diphenylphosphine oxide and di(3-aminophenyl)methylphosphine oxide via in situ polymerization of monomeric reactant method. The amide–ester solutions were impregnated with carbon fiber (Cf ) and quartz fiber (Qf ) cloth to give high quality prepregs that were then thermally cured to yield the Cf -reinforced polyimide (PI) composite (Cf /PI) and Qf -reinforced PI composite (Qf /PI), respectively. The Cf /PI composites showed high mechanical properties with a flexural strength of 1554 ± 93 MPa, a flexural modulus of 112 ± 3 GPa and an interlayer shear strength of 90 ± 5 MPa, respectively. The atomic oxygen (AO) resistances of the neat resins and composites were evaluated on a ground-based simulation facility. Experimental results indicated that the P structures offer PIs with 55–75% lower weight losses and a self-healing property. The fiber-reinforced composites showed further lower erosion rates than neat resins. In addition, the effects of calcdM n ‾ and P loadings on the melt processabilities of the B-staged imide oligomers and the AO resistance of the cured PIs were systematically investigated.